Audit Keselamatan Jalan (Studi Kasus Jalan Sutoyo Patah Kota Bengkulu) - Daryon Mulyadi (Jurusan T.Sipil Fakultas Teknik UMY, 2011)
Audit Keselamatan Jalan (Studi Kasus Jalan Sutoyo Patah Kota Bengkulu)